Evaluasi Kebijakan Kurikulum Merdeka pada Sekolah Menengah Atas di Kabupaten Merauke - Irawan, Andri; Yunitasari, Firda (Jurnal Administrasi Karya Dharma, 2025)
This study evaluates the implementation of the Merdeka Curriculum Policy in public senior high schools (SMA Negeri) in Merauke Regency using William N. Dunn’s six policy evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Employing a qualitative evaluative design, the study involved principals, teachers, supervisors, students, and parents selected through purposive sampling. Data were collected through in-depth interviews, classroom and P5 project observations, and analysis of school documents. The findings indicate that the Merdeka Curriculum is effective in enhancing student participation, creativity, and contextual learning in schools with adequate infrastructure, yet its effectiveness is uneven in schools located in peripheral areas. In terms of efficiency and adequacy, the policy has not been fully optimal due to limited ICT resources, varying teacher competencies, and diverse pedagogical needs of students. Equity issues are evident, as technological access, teacher training, and P5 opportunities differ significantly between urban and rural schools. The policy is responsive to student learning needs but less responsive to the needs of teachers and schools, which experience increased administrative burdens and limited technical support. Although appropriate philosophically for the Merauke context, operational challenges hinder its full relevance. Overall, the Merdeka Curriculum holds strong transformative potential but requires strengthened structural support to ensure effective and equitable implementation.